Observation of the clinical characteristics of chronic diarrhea in children and evaluation of the prognostic value of nutritional and immune indicators - Hao, JianYun; Ma, Xin; Gong, YouZhe; Zhu, Dan; Ning, HuiJuan; Zhong, XueMei (Journal of Medical Biochemistry, 2024)
Objective: This research targeted to assess the clinical characteristics of chronic diarrhea in children, and explore the prognostic value of nutritional status and immune indicators.Methods: A total of 190 patients with chronic diarrhea from January 2017 to June 2020 were enrolled to analyze their epidemiology. The patients were divided into a better prognosis group (cured, improved) and a poor prognosis group (uncured), followed by determining the diagnostic efficacy of nutritional status and immune indicators in the prognosis of children with chronic diarrhea.Results: Most of the patients were 0-3 years old (74.2%), of which 54.3% were less than 1 year old, and the highest proportion (48.95%) had diarrhea with a course of 1 to 2 months. The levels of albumin, immunoglobulin G (IgG), IgA and IgM, as well as albumin, globulin and the ratio of albumin to globulin in the better prognosis group were higher than those in the poor prognosis group. The AUC (area under the curve) of the combined detection in evaluating the prognosis of children with chronic diarrhea was greater than that of the albumin and globulin alone (P < 0.05). IgG ≥ 10.05g/L and IgA ≥ 7.72g/L were protective factors affecting the prognosis of children with chronic diarrhea.Conclusion: Children with chronic diarrhea are mainly infants and young children with various clinical symptoms, and are prone to comorbidities such as malnutrition, anemia, hypoalbuminemia, and impaired immune function. The combined detection of nutritional status and immune indicators in children is of value in evaluating the prognosis of children.
Keywords: Chronic diarrhea; Clinical features; Nutritional status; Immune indicators; Prognosis